ТҮРКИЙ ФИЛОЛОГИЯ ИЛИМИНДЕГИ БЕЛГИЛИ ТУЛҒА - Қуттымуратова, Ы.А. (ILIM hám JÁMIYET, 2025)
The article describes the activities of the famous scientist and linguist Anarkul Salkynbay, who presented scientific works on cognitive science, linguoculturology, language history, word formation, grammar, lexicology, language and culture in Kazakh linguistics. The scientific works of the scientist written for students in the discipline “history of the Kazakh language”, “history of language and culture” were also analyzed.